Haemonchus contortus-Sheep relationship: A review. - Angulo Cubillán, Francisco; García Coiradas, Leticia; Cuquerella, Montserrat; De la Fuente, Concepción; Alunda, José (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Haemonchosis, caused by the abomasal nematode Haemonchus contortus, is among the most relevant parasitic diseases of small ruminants all over the world. The infections are responsible for anemic and bad digestion/absorption syndromes causing the death of severely infected animals in acute cases and the reduction of production scores in the chronic forms of the disease. The keys for the appearance of the disease include the biological behavior of the helminth and mechanisms of pathogenesis, besides the host”™s response. The updated knowledge of these aspects would result in a higher efficiency of diagnostic and control methods, thus reducing the risks of appearance of the disease. In the present review, several aspects of the sheep - H. contortus relationship are analyzed with the aim of reducing the impact of this parasitosis on livestock health and productivity.